УДОСКОНАЛЕННЯ ОРГАНІЗАЦІЇ НАДАННЯ СОЦІАЛЬНИХ ПОСЛУГ СПЕЦІАЛІСТАМ ФАРМАЦІЇ - Зарічкова, М. В. (Фармацевтичний часопис, 2015)
IMPROVEMENT OF THE ORGANIZATION OF PROVIDING THE SOCIAL SERVICES FOR SPECIALISTS PHARMACY M. V. Zarichkova InstituteofPharmacyProfessionals Qualification Improvement (IPHPQI), NationalUniversityofPharmacy, Kharkiv Summary: the main components of the system of social services (SS) for specialists’ pharmacy, namely the quality, the monitoring, the control and the evaluation of SS were considered. SS as an economic category was analyzed and outlined its basic properties. The differences of SS and material assistance were given. It was theoretically proved necessity of improvement some of the terms, including «social services», «monitoring of social services», «quality of social services for specialists pharmacy» and others. The algorithm for monitoring, control and evaluation of SS was developed. It was proposed to consider these components as a chain of «Monitoring of social services (MSS) - Control of Social Services (CSS) - Evaluation of Social Services (ESS)». It was investigated the legislative support of provision of SS and on its basis proposed to develop the unified standard of SS for specialists pharmacy. Keywords: social protection of specialists pharmacy, pharmaceutical industry, social services, monitoring of social services, control of social services, evaluation of social services. Introduction. The important aspect in providing SS specialists pharmacy is the implementation of the institutional analysis of the production sector SS of an administrative-territorial unit. Particular attention is given to study ought the state's role in the formation and development of the sector SS; study the scope and structure of the sector SS relevant administrative units, mechanisms and forms of interaction between its elements, potential and resources of organizations to provide the necessary SS. This requires comprehensive research and detailed description the sector SS. The analysis of the scope of the provision of SS may be useful to identify of social groups’ pharmacy professionals who today feel the need in social protection and the relevant SS [1, 2]. Research methods. The basis of the research served as the requirements legislative and normative acts the system for providing SS in Ukraine; domestic scientific achievements of the organization and economics of pharmacy. During research the have been used the modern scientific methods: comparison (generalization legislative base on providing SS), logical (research of dynamics of changes in the provision of SS), historical analysis and more. We have been analyzed the existing scientific publications of foreign and domestic authors, who covered the issues related to social protection. Thus, the problems of social security of the population studied, particularly domestic scientists - Kotvitska A.A., Posylkina A.V., Nemchenko A.S. etc. The analysis of the literature has shown that the attention to the use of SS inUkraine started quite recently, and experience in providing SS for specialists’ pharmacy is an innovative. Results and discussion. The development of the private sector social service is extremely slow inUkraine. This is associated with the imperfection of the normative base which does not allow developing non government social services, in particular given the sector specific. The development of the private sector in the social protection specialist pharmacy (SPSPh) ofUkraine is a social problem which requires immediate resolution. The demand for alternative social care of professionals pharmacy has been around a long time, but appropriate conditions for its implementation has not created [1]. Developed industries countries use different models of social services, which are promising for application inUkraine. The foreign experience of the private sector to provide SS demonstrates the significant achievements in this regard. Is necessary to note that in all these countries the right to providing SS guaranteed by the State and derive social competition. Typically in private institutions SS is cheaper than in public. However, the recipients seeking to use the SS of state institutions because the quality of SS is higher. Conclusions. 1. Has been analyzed the existing experience of SS in Ukraine and abroad and the possibility of their use in the trade unions and other organizations that deal with social protection specialist pharmacy has been established. It was found that to date is missing effective mechanism to provide of SS specialists pharmacy in the relevant administrative units territorially because we consider it necessary to create a single register of SS for pharmacy professionals. 2. The basic criterion features of SS were analyzed and brief description of them was given, with highlighted as features of each criterion. 3. It was analyzed the legislative and normative base which regulates the system of SS and discovered necessity of improvement of some terminological definition of concepts such as "social service", "monitoring of social services", "quality of social services for specialists pharmacy " and so on. 4. It was studied the system of SS inUkraineand found that it is reasonable to improve the organization of monitoring, control and evaluation of SS. To summarize the actions in this direction was suggested to consider these components as a chain "MSS - CSS - ESS." 5. The resulted of studies have demonstrated that there exists necessity of development of system of SS standards that provide adequate standard of living specialists pharmacy and correspond to the European standards. Considering this, the basis of social protection specialist pharmacy is necessary to not establish subsistence minimum, as specified in the applicable social laws and social standards on the basis of pharmacy professionals.